Sensibilização de professores e alunos para a prevenção de uso abusivo de drogas e sexo desprotegido - Dallo, Luana [UNESP] (2014)
didn't open space during your class for the discussion about the questions of doubt. Thus, it is concluded that it is necessary a recognition of society regarding the importance of working these themes in school and include them in the initial training in the areas of education and health, in addition to the process of continuing education for educators. Finally, it points out that the youth protagonism in health education can become an effective proponent for prevention of risk behaviours in school when there are social recognition of this proposal.